Municipal management and quality of public service in the municipality of Pueblo Libre, 2021 - Ruiz Gutierrez, Miguel Stefano (2022)
This article aims to explore the relationship between municipal management and quality of service provided by the District Municipality of Pueblo Libre, Lima-Peru, in the management period 2019-2021. This research was correlational, descriptive, non-experimental and cross-sectional in scope. The population and sample consisted of 31 municipal managers and 31 representatives of neighborhood councils, these elected by residents of the district; to whom two separate questionnaires were applied to collect information, a first questionnaire was applied to the 31 managers to evaluate the one they had on municipal management and another questionnaire to the 31 representatives of the neighborhood councils to evaluate the quality of the municipal service based on the Serviqual model. Descriptive statistics and inferential statistics were used for data analysis using the SPSS 25 statistical software. The results show that there is a direct and significant relationship between municipal management and public service quality with p=0.000 and r=0.928. Among the most significant results found were that the level of municipal management is perceived as very deficient in 0%, deficient in 6.5%, acceptable in 35.5%, good in 41% and excellent in 5%; Regarding the level of quality of service as very poor in 10.1%, poor in 40.6%, acceptable in 34%, good in 12.8% and excellent in 2.5%. The results show the existence of a gap between the perceptions of the work of public officials and the expectations of citizens, a gap that determined the quality of the municipal public service.